Pengaruh Penambahan Ion Mg2+ Terhadap Kandungan Lipid Fitoplankton Chlorella vulgaris Sebagai Bahan Baku Pembuatan Biodiesel dengan Metode Ultrasonik - Alfani M Datu; Indah Raya; Muhammad Zakir (Marina Chimica Acta, 2013)
An investigation on the effect   of Mg2+     on its lipid content from phytoplankton Chlorella vulgaris as a raw material for producing biodiesel by ultrasonic method has been carried out. The  results  showed  that  Mg2+   is  good  as  a  nutrient  for  phytoplankton.    The  optimum concentration was 0.4 ppm. Total of dry biomass was 32.7902 grams. Lipid was extracted  by ultrasonic method using ethanol 95% as solvent. Biodiesels were syntesized in two steps namely esterification by methanol solvent and H2SO4 as catalyst, folowed by transesterification by using methanol solvent with KOH as a catalyst. Total of biodiesel made was 11.5727 grams and the yield  was  35.29%. The result  of  biodiesel  characterised  in term of  physical  and  chemical characteristics including:   density, viscosity, free fatty acid, saponification value, and iodine value, respectively.   Result of the analysis showed that biodiesel characteristics have fulfilled standard the American  Society for Testing and  Materials  (ASTM D6751), except  value of density and Free Fatty Acid.